A Biological Study of Larvae and Adult Hemonchus contortus in Goat - Yuswandi Yuswandi; Rika Yuniar S (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
A biological study of larvae and adult Hemonchus contortus was carried out in goat. The aims of this study were to know the capability of the infective larvae (L3) development to adult, and the prepaten period of H. contortus. A number of 14 goat abomasum collected from Ngampilan Slaughterhouse, Yogyakarta Province was used as source of H. contortus. Eggs worm were collected from direct surgery of the H. contortus in physiological saline. The egg development of H. contortus to the L3 stadium was carried out by a modification Harada-Morito, whereas the development of the L3 to adult and the prepaten period were studied in the goat asexperimental animal in vivo. Before the goat necropsied, the diagnosis of H. contortus egg was done every two day post infection and started two weeks after infection. The data was analyzed descriptively. The results showed that the capability of the egg development of the worm to the L3 stadium was 0,33%, the capability of the L3 development to adult was 32,42%, and the prepaten period of H. contortus was 21 days.